Hemograma, metabolismo oxidativo dos neutrófilos e peroxidação lipídica em cadelas com piometra por Escherichia coli - Emanuelli, Mauren Picada (2007)
Pyometra is an infectious disease predominating in adult female dogs during diestrus. It is caused by an intra uterine bacterial infection leading from a mild to a severe bacteremia and toxemia. In hematological parameters a severe leukocytosis and anemia usually are presents. The objective of this study was to evaluate complete blood count, neutrophil oxidative metabolism by nitroblue tetrazolium test (NBT) and lipid peroxidation using thiobarbituric acid reactive substances assay (TBARS). Twenty adult female dogs from 2 to 14 years old were used. All animals were allocated in two different groups. In group 1 E. coli pyometra diagnosed animals (n=12) and in group 2 only clinically healthy female dogs (n=8). There were significant lower values in red blood cell, packed cell volume and hemoglobin in group 1 animals than those in group 2 (control). A significant increase in total plasma protein and total leukocytes (segmented and band neutrophils and monocytes) occurred in group 1 when comparing to control. In NBT there was also an increase in group 1. But TBARS did not show a significant difference between groups. These results evidenced that adult female dogs with pyometra by E.coli show a normocyitic normocromic anemia and leukocytosis characterized by neutrophilia with a left shift. The NBT raise only indicate a neutrophil activity increased.